FILSAFAT KOSMOLOGI JAWA YANG DIWUJUDKAN: Analisis Hermeneutika-Fenomenologis terhadap Siklus Hidup dalam Tari Topeng Cirebon - Nur Indah Septia Ningsih; Wasino, Wasino; Arghita Aricindy; Tri Astuti (Universitas Banda Naira, 2025)
This study characterized the Cirebon Mask Dance as a sophisticated system of embodied philosophy, rather than merely a performance art. Employing an integrated hermeneutic-phenomenological approach, the research analyzed the dance's sequential progression through the five mask archetypes: Panji, Samba, Rumyang, Tumenggung, and Kelana, as a choreographed metaphysical argument. A tripartite analysis of movement semiotics, symbolic hermeneutics, and philosophical contextualization revealed that the dance articulated the Javanese cosmological principle of sangkan paraning dumadi (the origin and destination of being). The findings demonstrated that each mask embodied a distinct stage in human spiritual development, commencing with the undifferentiated purity of Panji, progressing through worldly exploration (Samba), symbolic mediation (Rumyang), and structured responsibility (Tumenggung), culminating in the transformative crisis of Kelana. Collectively, this sequence mapped a philosophical journey in which physical practice was transformed into coherent metaphysical discourse. This study contributed to the field of performance philosophy by providing a methodological framework, while simultaneously validating the Cirebon Mask Dance as a vital and enduring intellectual heritage